Forced labor and denial of freedom: the sources, history, legal and organizational patterns of punishment - Krasikau, Vladimir (Journal of the Belarusian State University. Law, 2019)
The article examines the patterns of occurrence and history of forced labour as social protection measures in the criminal legislation of the Soviet republics (on the example of Russia and Belarus) since their formation in the early twentieth century, influenced the formation of punishments not related to deprivation of liberty. Substantiated conclusions about the regularities of the influence of economic, political, social conditions and management activities of the subject of performance to the formation of this legal institution, its mode of execution and use of means of correction for convicts.
Keywords: measure of social protection; punishment; imprisonment; forced labor; the regime; educational work with prisoners; the subject of punishment; individual punishment; a progressive system of punishment